Correlation between Systemic Arterial Hypertension and Bone Morphogenetic Protein-2 in Central Obese Non-Diabetic Men with Evidence of Coronary Artery Calcification - Antonia Anna Lukito; Allen Widyasanto; Trilis Yulianti; Rusli Muljadi; Andi Wijaya; Peter Kabo; Syakib Bakri (The Indonesian Biomedical Journal, 2011)
BACKGROUND: Previous studies have confirmed separately the relationship between obesity, insulin-resistance, hypertension and bone morphogenetic protein-2 (BMP-2) with coronary artery calcification, a parameter of subclinical atherosclerosis. It was also reported that BMPs may function as proinflammatory, prohypertensive and proatherogenic mediators. The study aimed to assess the correlation between systemic hypertension and BMP-2 plasma concentration in central-obese non-diabetic men with evidence of coronary artery calcification.METHODS: This was a cross sectional study on 60 central-obese non-diabetic men, of an average age of 55.2 years, with evidence of coronary calcification, who came for health check-up and met the inclusion criteria consecutively as defined by waist circumference >90 cm and fasting blood glucose <126 mg/dL. Coronary calcification was defined by coronary artery calcium (CAC) score ≥10 Agatson-unit Dual Source 64 slice CT scan.RESULTS: There is positive correlation between hypertension and BMP-2 in central-obese non-diabetic men with evidence of coronary artery calcification. BMP-2 plasma concentration was higher in the hypertensive subjects. The correlation was stronger in younger (<55 years old) subjects and subjects with insulin-resitance.KEYWORDS: hypertension, BMP-2, coronary calcification, central obesity, age, insulin resistance